China tourists' experiences with longhouse homestays in Sarawak / Liping Wang... [et al.] - Wang, Liping; Hu, Mingqi; Guo, Zhenfeng; Sun, Peipei; Geng, Fangmei; Voon, Booho (Universiti Teknologi MARA Cawangan Sarawak, 2019)
There are many types of eco-cultural tourism products and the homestays are popular in Malaysia. In Sarawak, the Longhouse homestay programmes are attractive to foreign tourists and the tourists from China are great potential customers. Hence, the expectations and experiences of the China tourists need to be well understood as they might have different expectations. The main objective of this exploratory research was to identify the important dimensions and specific aspects of the China tourists' experiences with the longhouse homestays, specifically with a Bidayuh longhouse in Kuching. It was a qualitative research using site visits and focus group interview. The visits and interviews involved five China tourists. The contents of the interviews were analyzed and their experiences were categorized to form more than 15 dimensions with the respective items. The fifteen dimensions were, namely: Journey, ICT, Communication with Tourist, Culture, Moral, Education, Tourist Service, Tourist Engagement, Homestay Management, Food and Beverages, Cleanliness, Nature, Built Environment, Art, and Security. Besides, their suggestions were also obtained for the homestay programme to be improved. The limitations of this research and direction for future research were also discussed.